A bifunctional 2, 2′:6′, 2″-terpyridine-based ligand for ratiometric Cu(II) sensing. Issue 7 (3rd April 2017) - Abdalrahman, M. A.; Abebe, F.; Briggs, J.; Kassel, W. S.; Burdette, S. C.; Seitz, W. R.; Planalp, R. P.
Abstract: Synthesis and characterization of the bifunctional sensor receptor ligand N-([2, 2′:6′, 2″-terpyridine]-4′-yl)methyl)-N-propylacrylamide (1 ) and the model ligand N-([2, 2′:6′, 2″-terpyridine]-4′-yl)methyl)-N-propylisobutyramide (2 ) are described. Ligand1 is a receptor for Cu(II) that is copolymerizable with N-isopropylacrylamide giving a ratiometric sensor of weakly bound Cu(II) in environmental waters. Ligand2 is a model for copolymerized1 whereby the reactive acrylamide group is replaced by isobutyramide. Solution speciation of complexes of Cu(II) and Zn(II) with2 were investigated spectroscopically and their solid-state structures were studied through single-crystal X-ray diffraction. Solution UV–vis and fluorescence studies show a preference of2 toward Cu(II) over Na(I), Zn(II), Cu(II), Co(II), Mn(II), Ni(II), Cd(II), and Pb(II) in accord with the Irving–Williams series and other coordination principles. Solution speciation determined in a weakly coordinating aqueous-organic (60 : 40 DMF/H2 O) medium indicates 1 : 1 Cu(II):2 binding as desired in that formation of [Cu(2 )2 ] 2+ would crosslink the polymer sensor. The crystal structures of [Cu(2 )(NO3 )2 ] and [Zn(2 )(NO3 )2 ]·MeOH·1/2Et2 O display distorted octahedral geometries where2 coordinates meridionally and two nitrate groups occupy the remaining sites around the metal center. Graphical Abstract: